Cognitive-behavioral attitudes formed by trauma of political repressions and their family inheritance - Gronskiy Andrey (Психология и Психотерапия Семьи, 2021)
The article is based on the empirical research of post-totalitarian attitudes formed as a result of collective trauma of political repression in USSR and their ways of intergenerational transmission. 146 university students took part in the study. The average age was 20. Survey tools were used compiled by us post-totalitarian attitudes inventory. It was revealed that all respondents know about political repression in the USSR, 40% know that there were repressed relatives in their family. Nonetheless the attitude towards political repressions in the sample was heterogeneous. 60% of respondents refer to political repression with unconditional condemnation. 21% believe that repression was necessary. 40%, in general, have a positive attitude towards the period of Stalin's rule, despite particular disadvantages. As for attitudes, transmitted by older generation, 73% of respondents have heard from their parents or grandparents verbal messages about the inability to influence the political life of the country. 84% indicated that their close relatives avoid criticizing the actions of the state authorities in a public setting. 62% indicated that political issues are rarely discussed in parental families. As regards their own cognitive attitudes, emotional and behavioral reactions, half (52%) of respondents have a vague fear of a repeat of mass political repression. Almost half (46%) of the survey participants believe that although the days of Stalinism are over, they need to control their statements and actions for their own safety. At the same time, the attitude of helplessness and powerlessness regarding social life is much less represented in the student sample than in the generation of their parents.